A CB-SVPWM control strategy for neutral-poin voltage balancing in three-level NPC inverters - Hussapong Kitidet (2018)
© 2017 IEEE. For the three-level neutral-point-clamped inverters, neutral point voltage balancing control is necessary for proper operation. This paper presents a balancing control strategy of the neutral-point voltage with a closed-loop dc-link mid-point capacitor voltage control. Instead of the adjustable pulse-width switching sequence of the small voltage vector with the space-vector-based concept, it is only done by mathematical analysis of the neutral-point current coordinated with the carrier-based pulse width modulation concept to find out the relative DC offset added into the continuous modulating signals. This is in order to regulate the inverter operation for solving the unbalanced dc voltages of two split capacitors. The distinctive simplicity of the proposed control strategy is the use of the DC-side diagnosis along with a convenient P controller. The performance and feasibility of the proposed control strategy are verified by detailed simulation results.